The Impact of Stress Factors Related to the War in Ukraine on the Mental Health of Young People (A Case Study of 3-4 Year Old Students at the National University of Kyiv-Mohyla Academy) - Kraskov, Oleksandr (Psychosomatic Medicine and General Practice, 2024)
Background: In recent years, Ukraine has experienced profound socio-political upheavals, exacerbated by a full-scale war that has lasted for over two years. This protracted war has not only left physical scars on the body of our nation, but has also caused significant psychological trauma, especially among young people. As the war continues, understanding the extent of the impact of war-related stressors on the mental health of Ukrainians has become imperative, especially in academic settings. Methods: The research has cross-sectional design. The duration of the field phase of the study was 3 weeks from 08 to 28 April 2024. The sample size was 217 students (95% confidence level, 6.5% margin of error with a total population of 2340 students). An online survey was used to collect quantitative data, including demographic data, a list of specific stressors, and the PCL-5 scale. Results: Among the respondents, 62.6% of females and 36.5% of males had PTSD symptoms (p-value 0.004). Age, course, faculty, specialty, region of residence, type of settlement, employment, change of residence did not have a statistically significant relationship with the presence of PTSD symptoms in the study sample. The most common stress factor - "Ongoing threat of negative events" - is present in 98.2% of respondents. The least common is "Bodily injury" - 63.6%. The highest stress level (8.3/10) was caused by the factor "Death/serious injury of a family member or close friend". The lowest (4.4/10) was "Sound of air raid sirens". Conclusion: Students of the National University of Kyiv-Mohyla Academy are experiencing an increased level of stress due to the war in Ukraine, and this stress affects their mental health and leads to the development of symptoms of post-traumatic stress disorder. A statistically significant relationship was found between each of the stressors studied and the respondents' PTSD symptoms.